Simulação da concentração de material particulado inalável de origem veicular em uma interseção sinalizada de Uberlândia-MG - Fernandes, Marcus Vinícius de Oliveira (2013)
Among the environmental impacts arising from the massive urban space occupation the atmospheric pollution has been pointed and associated to high rate of morbidity and mortality of the human beings. The economic and social development of the populations can induce the increment of the atmospheric emissions, especially those deriving from the automotive fleet exhausts. It constitutes diffuse sources of various pollutants as the inhalable particles (PM10), whose the harmful effects are the most important justification for monitoring it in the urban centres. The quantification of the suspended particles in the atmosphere of the city of Uberlândia-MG is carried by the Chemical Engineering Faculty of the Federal University of Uberlândia since 2003 near to the central bus station. The main objective of this work was to use the Gaussian model CAL3QHC in predicting the concentration levels of PM10 originated from vehicular sources for the year 2012 and then validating the results by comparing with the experimental data. Considering that the climatic conditions affects decisively the air quality was preceded the characterization of the climate of the city and its influence in the inhalable particulate pollution for the 2003 to 2012 period. The results from the analysis of the climatic variables has shown the existence of critical periods of pollution in the dry seasons of the year in which the patterns of PM10 established by the National Environment Council was exceeded. The results reached in the numeric simulation of PM10 concentrations revealed the capability of the model CAL3QHC in responding the wind speed and direction variation and the moderated performance of the model on the assumptions. The inaccuracy of the model were assigned to the inconsistence of some variables as the vehicular emission factor and the background concentrations.